2010
DOI: 10.1016/j.bpj.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Mathematical Models of Slow Wave Entrainment in Wild-Type and 5-HT2B Knockout Mice with Altered Interstitial Cells of Cajal Networks

Abstract: Gastrointestinal slow waves are generated within networks of interstitial cells of Cajal (ICCs). In the intact tissue, slow waves are entrained to neighboring ICCs with higher intrinsic frequencies, leading to active propagation of slow waves. Degradation of ICC networks in humans is associated with motility disorders; however, the pathophysiological mechanisms of this relationship are uncertain. A recently developed biophysically based mathematical model of ICC was adopted and updated to simulate entrainment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(107 citation statements)
references
References 32 publications
(63 reference statements)
4
103
0
Order By: Relevance
“…5-HT promotes the survival of ICC cells in culture via actions on 5-HT 2B receptors 130 , and the density of ICC is decreased in 5-HT 2B receptor deficient mice. Modeling of these changes suggests that alterations of the ICC network would impair slow wave propagation and ultimately motility and transit in the intestines 131 .…”
Section: Functions Of 5-ht In the Gastrointestinal Tractmentioning
confidence: 99%
“…5-HT promotes the survival of ICC cells in culture via actions on 5-HT 2B receptors 130 , and the density of ICC is decreased in 5-HT 2B receptor deficient mice. Modeling of these changes suggests that alterations of the ICC network would impair slow wave propagation and ultimately motility and transit in the intestines 131 .…”
Section: Functions Of 5-ht In the Gastrointestinal Tractmentioning
confidence: 99%
“…Previous studies have simulated tissue-specific slow wave propagation over ICC networks by coupling imaging data with a modified biophysically-based Corrias and Buist cell model [12] embedded within a continuum modeling framework [11, 13]. However, this methodology is computationally expensive [13], mainly due to the large number of equations and parameters present in the cell model, and hence difficulties exist in up-scaling these simulations to larger multiscale simulation studies.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Cholinergic regulation is also known to modulate ICC-IM frequencies, potentially inducing arrhythmias, 23 and a role for autonomic neuropathy in aberrant slow wave initiation therefore deserves further investigation. In terms of conduction abnormalities, biophysically-based modeling studies have shown that slowed haphazard conduction occurs in states of ICC loss, 24 potentially promoting arrhythmias. In addition, conduction blocks must result when ICC loss falls below a critical threshold.…”
Section: The Pathological Basis For Arrhythmias In Gastroparesismentioning
confidence: 99%